Intestinal mucosal mast cells: isolation from rat lamina propria and purification using unit gravity velocity sedimentation. - Lee, T D (1985)
Mucosal mast cell (MMC) suspensions obtained from the rat intestinal lamina propria by collagenase digestion (35.2 +/- 3.2% MMC) were enriched to 65.5 +/- 5.2% MMC by the use of a discontinuous gradient (30%/80%) of Percoll. Further purification to 95.7 +/- 1.3% MMC was achieved using velocity sedimentation at unit gravity (Sta-Put). Analysis of the cells throughout the purification procedure confirms that the purified MMC are representative of the MMC in the initial isolated cell suspension. No differences were seen in terms of size, histamine content, protease content and responsiveness to secretagogues among the initial isolated population, the Percoll-enriched population and the Sta-Put-purified population. This study represents a major advance in mast cell research in that, for the first time, mast cells isolated from a homogeneous in vivo mucosal source have been obtained at levels of purity sufficient for specific biochemical characterization. Such characterization will aid in the interpretation of the role of MMC in disease and will provide a firm basis of knowledge of the form and function of intestinal MMC for comparison with mast cells derived from other mucosal sites or cultured in vitro from various organs.